Ethanolic Fenugreek Extract: Its Molecular Mechanisms against Skin Aging and the Enhanced Functions by Nanoencapsulation - Waleewan Eaknai; Phichaporn Bunwatcharaphansakun; Chutikorn Phungbun; Angkana Jantimaporn; Sasikan Chaisri; Suwimon Boonrungsiman; Ubonthip Nimmannit; Mattaka Khongkow (MDPI AG, 2022)
Fenugreek, or Trigonella foenum-graecum L. (family Leguminosae) seeds, are typically used as food supplements to increase postnatal lactation. Fenugreek extract displays antioxidative and anti-inflammatory properties, but its mechanisms against skin aging have not been exploited. In this research, we are the first to define an in vitro collagenase inhibitory activity of fenugreek extract (IC50 = 0.57 ± 0.02 mg/mL), which is 2.6 times more potent than vitamin C (IC50 = 1.46 mg/mL). Nanoencapsulation has been applied to improve the extract stability, and subsequently enhanced its bioactivities. Liponiosome encapsulating fenugreek extract (LNF) was prepared using a high-speed homogenizer, resulting in homogeneous spherical nanoparticles with sizes in the range of 174.7 ± 49.2 nm, 0.26 ± 0.04 in PdI, and 46.6 ± 7.4% of entrapment efficiency. LNF formulation significantly facilitated a sustained release and significantly enhanced skin penetration over the extracts, suggesting a potential use of LNF for transdermal delivery. The formulated LNF was highly stable, not toxic to human fibroblast, and was able to enhance cell viability, collagen production, and inhibit MMP1, MMP9, IL-6, and IL-8 secretions compared to the extract in the co-cultured skin model. Therefore, ethanolic fenugreek extract and its developed LNF display molecular mechanisms against skin aging and could potentially be used as an innovative ingredient for the prevention of skin aging.